Reading Assessment Tool “LexiMetr” for Russian-Speaking Primary School Students - Nina S. Zdorova; Vladislava N. Staroverova; Anastasiya A. Lopukhina; Diana B. Dzhonboboeva; Evgenia A. Pareshina; Ekaterina R. Shestakova; Varvara A. Gmyrina; Elizaveta P. Dmitrova; Olga V. Dragoy (Вопросы образования, 2025)
The present article describes the creation and standardization of the “LexiMetr” reading assessment tool, designed to evaluate reading skills in Russian-speaking primary school students. A distinguishing feature of the “LexiMetr” test is its linguistic validity. Namely, the test comprises two texts to read out-loud, controlled for their objective complexity based on a range of psycholinguistic features. The test is created in a user-oriented digital application for tablets.